Malaria Burden in Pregnancy at Mulago National Referral Hospital in Kampala, Uganda - Namusoke, Fatuma; Rasti, Niloofar; Kironde, Fred; Wahlgren, Mats; Mirembe, Florence (Malaria Research and Treatment, 2020)
Pregnancy-associated malaria is a major global health concern. To assess the Plasmodium falciparum burden in pregnancy we conducted a cross-sectional study atMulago Hospital in Kampala, Uganda.Malaria prevalence by each of three measures—peripheral smear, placental smear, and placental histology was 9%(35/391), 11.3% (44/389), and 13.9% (53/382) respectively. Together, smear and histology data yielded an infection rate of 15.5% (59/380) of active infections and 4.5% (17/380) of past infections; hence 20% had been or were infected when giving birth. A crude parity dependency was observed with main burden being concentrated in gravidae 1 through gravidae 3. Twenty-two percent were afflicted by anaemia and 12.2% delivered low birthweight babies. Active placental infection and anaemia showed strong association (OR = 2.8) whereas parity and placental infection had an interactive effect on mean birthweight (P = .036). Primigravidae with active infection and multigravidae with past infection delivered on average lighter babies. Use of bednet protected significantly against infection (OR = 0.56) whilst increased haemoglobin level protected against lowbirthweight (OR = 0.83) irrespective of infection status. Albeit a high attendance at antenatal clinics (96.8%), there was a poor coverage of insecticide-treated nets (32%) and intermittent preventive antimalarial treatment (41.5%).
Keywords: Malaria; Pregnancy; Mulago National Referral Hospital; Uganda